2022
DOI: 10.3389/fendo.2022.987081
|View full text |Cite
|
Sign up to set email alerts
|

Real-world national trends and socio-economic factors preference of sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists in China

Abstract: BackgroundsRobust evidence have demonstrated the beneficial effect of Sodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) in T2D patients with cardiovascular diseases and chronic kidney disease. Multiple studies analyzed patterns and predictors of SGLT2i and GLP-1RA in the US, Europe and worldwide. However, there is no study about the utilization of these two classes of drugs in real-world in China.MethodA total of 181743 prescriptions of SGLT2i and 59720 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This finding was consistent with the overall dramatic rise in SGLT2i use in China. A real-world study which enrolled a total of 181,743 prescriptions of SGLT2i in China and showed the annual number of prescriptions of SGLT2i dramatically increased to approximately 140 folds from 2018 to 2021 [ 17 ]. The massive increase was closely associated with robust evidence showing the beneficial effects of SGLT2i in T2D with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with the overall dramatic rise in SGLT2i use in China. A real-world study which enrolled a total of 181,743 prescriptions of SGLT2i in China and showed the annual number of prescriptions of SGLT2i dramatically increased to approximately 140 folds from 2018 to 2021 [ 17 ]. The massive increase was closely associated with robust evidence showing the beneficial effects of SGLT2i in T2D with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of T2D as well as the incidence of CVD in diabetic populations have been rising rapidly in China (13)(14)(15). Meanwhile, the utilization of novel anti-hyperglycemic agents such as SGLT-2i, GLP-1RA, and DPP-4i has also rapidly increased among Chinese diabetic patients (16,17). These novel antihyperglycemic agents possess multiple pleiotropic effects, particularly, for SGLT-2i and GLP-1RA.…”
Section: Introductionmentioning
confidence: 99%